2003
DOI: 10.1046/j.1463-5224.2003.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Schirmer tear test results in normal horses and ponies: effect of age, season, environment, sex, time of day and placement of strips

Abstract: Tear production was evaluated in 39 horses and 29 ponies using Schirmer tear test strips to determine whether diurnal or weekly fluctuations occur, whether location of strip placement has an effect, if values are the same for both eyes in an animal and whether sex, age, stabling vs. pasture and winter vs. summer had an effect. There was no test in which the raw score was less than 10 mm, although there were many occasions where tear wetting exceeded 35 mm. Analysis of the raw (continuous) scores by linear regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
66
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 10 publications
9
66
2
1
Order By: Relevance
“…Schirmer tear test I measurements assess basal and reflex tearing and, despite the wide range of tear production measurements obtained in the goats, the mean results are comparable to those observed in dogs, cats, wildebeests, oryxes, ibexes and rhinoceroses 29–31 . Although the ranges overlap, tear production in the goats is lower than measurements in horses and cattle 15,32–35 …”
Section: Discussionmentioning
confidence: 63%
“…Schirmer tear test I measurements assess basal and reflex tearing and, despite the wide range of tear production measurements obtained in the goats, the mean results are comparable to those observed in dogs, cats, wildebeests, oryxes, ibexes and rhinoceroses 29–31 . Although the ranges overlap, tear production in the goats is lower than measurements in horses and cattle 15,32–35 …”
Section: Discussionmentioning
confidence: 63%
“…The more commonly used STT I measures the basal and reflex tear production. The STT II on the other hand evaluates basal tear production after topical application of an anesthetic and is of predictive values in animals with corneal ulceration which do not tolerate the STT I 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…In the study of other physiological parameters, the pattern of diurnal variation was found to be affected by a number of endogenous and exogenous factors such as age, 7,8 season, 9–11 feeding times and fasting, 12–14 isolation, 15 exercise, 16,17 electro‐magnetic field, 18,19 change in light intensity and environmental temperature 10 . Normal STT has recently been shown to be affected by age, gender, time of day, season, environmental condition and placement of strips 20,21 . The purpose of this study was to determine the daily rhythm of tear production in horses subjected to three different light/dark (L/D) schedules, to compare left eye and right eye, and to evaluate the influence of time and gender.…”
Section: Introductionmentioning
confidence: 99%